Public attitudes towards privacy in COVID-19 times in the Republic of Ireland: A pilot study. Issue 5 (3rd September 2021) - Bendechache, Malika; Lohar, Pintu; Xie, Guodong; Brennan, Rob; Trestian, Ramona; Celeste, Edoardo; Kapanova, Kristina; Jayasekera, Evgeniia; Tal, Irina
ABSTRACT: This research focuses on designing methods aimed at assessing Irish public attitudes regarding privacy in COVID-19 times and their influence on the adoption of COVID-19 spread control technology such as the COVID tracker app. The success of such technologies is dependent on their adoption rate and privacy concerns may be a factor delaying or preventing thus adoption. An online questionnaire was built to collect: demographic data, participant's general privacy profile using the Privacy Segmentation Index (PSI) which classifies individuals into 3 groups (privacy fundamentalists, pragmatists, and unconcerned), and the attitudes toward privacy in COVID-19 times. The questionnaire was shared via websites and social networks. The data was collected between 27/08/2020 to 27/9/2020. We received and analyzed 258 responses. The initial pilot study found that almost 73% of the respondents were pragmatists or unconcerned about privacy when it came to sharing their private data. Comparable results were obtained with other privacy studies that have employed PSI. The pilot indicates a huge increase, from 12% pre-pandemic to 61% during the pandemic, of people willing to share their data. The questionnaire developed following this study is further used in a national survey on privacy in COVID-19 times.